Hubungan Tingkat Pendidikan Orang Tua terhadap Prestasi Belajar Siswa di SMAN 1 Kintamani - I Kadek Restu Panji Nurjaya (Journal on Education, 2025)
Education aims to prepare students in non-academic and academic fields so that they can play an important role in life in the future. The aim of the research was to determine the educational level of parents of students in grades XI and XII IPS, to determine the learning achievement of students in grades XI and This type of research is research using qualitative data. This qualitative data is data collected in the form of words or sentences that refer to the quality of a situation, activity, event, etc. The results of the data presentation show that the education level of the students' parents is at a fairly high level. This is illustrated by the results of measuring the level of parental education. From the results above, it can be seen that there is a correlation between the level of parental education and the correlation between parental guidance and student achievement in Geography lessons.